In vitro conservation of Cape gooseberry through slow-growth nodal segment cultures - Rezende, Renata Alves Lara Silva (2018)
The objective of this work was to evaluate the effects of temperature and osmotic agents on the in vitro conservation of Cape gooseberry (Physalis peruviana). Temperatures at 18 and 25°C, as well as the osmotic agents sucrose, mannitol, and sorbitol were tested. A short-term in vitro conservation of Cape gooseberry can be achieved at 18°C, using 30 g L-1 sucrose.